Voices: Exploring the Experiences of Non-Mental Health Professionals Working with Mexican Immigrants Affected by Deportation - Anna Lopez; Ioana Boie (Journal for Social Action in Counseling and Psychology)
With large numbers of immigrants living in the United States and a recent increase in deportations, it is imperative that mental health professionals are aware of the implications involved in working with immigrants affected by deportation. The perspectives of non-mental health professionals working with immigrants are valuable in providing insight into the complexity of issues encountered when working with this population. The participants discussed perceptions, reactions, perceived mental health needs, and recommendations for working with Mexican immigrants.